Tech and me: an autoethnographic account of digital literacy as an identity performance - Daniel Clark (Association for Learning Technology, 2020)
This paper is an autoethnographic account of developing digital literacy, as seen through references to identity, both in direct and indirect relationship to digital technology. Conceiving of digital literacy as a process that includes identity change, and identity as constituted by actions performed, posts from my blog focusing on educational technology written between 2011 and 2019, are analysed and coded. An initial analysis uses a framework, which sees digital literacy as an interaction between skills, practices and identity. The findings highlight not only the importance of identity but also the need for a more detailed understanding of identity than the one provided by this model. Findings related to identity are then analysed further. In the process, four specific and contradictory themes are revealed - technology advocate, technology sceptic, technology adept and technology novice. In addition, the importance of other identity markers in relation to technology is explored. In the context of individuals and organisations prioritising the enhancement of digital literacy, this paper suggests that the role of identity in such enhancement is critical and is not sufficiently captured in current research and discussion.